Vertical and panoramic views: a new vocabulary of drone shots in cinematography - Noor, Firdaus; Widyastutieningrum, Sri Rochana; Sutrisno , Mudji; Ajidarma , Seno Gumira (Institut Seni Indonesia Surakarta, 2025)
This study aims to reveal how drones have entered the language of film, which essentially means how drones can contribute to new vocabulary in cinematography, especially regarding the type of shot in camera angles and framing. This study uses a qualitative approach with a post-phenomenological descriptive analysis method developed by Don Ihde. The data presented are moving image documentation produced by drone technology in twelve documentary films from the Ekspedisi Indonesia Biru series, each lasting approximately 50 minutes. The observation results of the number of drone shots analyzed in this study totaled 193 (one hundred ninety-three). The analysis process was then compared using Bordwell, Thompson, and Mascelli's theory to conceptualize film vocabulary as formal and stylistic techniques used in drone cinematography in the twelve documentary films of Ekspedisi Biru Indonesia. Two important findings were identified based on indicators not found in the basic rules, vocabulary, and cinematographic language practices that have become industry standards. First, two new words were found in the drone camera angle variable: Vertical and Panoramic. Second, in the framing variable based on size and distance, drone cinematography language still refers to cinematographic grammar practices established in a global consensus. The striking difference lies in the height of the camera position, which has become a distinctive visual style of drone cinematography. Further research is needed to develop drone technology to realize new linguistic efforts, particularly from the perspective of camera movement, which challenges the dominance of existing film language. In the future, drone technology will incorporate more advanced artificial intelligence algorithms to enhance real-time camera movement maneuvers and add non-human factors such as energy efficiency, collision avoidance, flight restrictions, and bandwidth improvement.